Latvijas valsts un sabiedrības izaicinājumi un risinājumi starptautiskā kontekstā (INTERFRAME-LV): Report of Abstracts - Latvijas Universitāte. 80. starptautiskā zinātniskā konference (Latvijas Universitāte. 80.starptautiskā zinātniskā konference, 2022)
The conference session aims to provide a platform/opportunity for scholars, researchers and professionals from different disciplinary backgrounds to meet, exchange ideas, findings, research results and discuss the topical issues related to the challenges for the Latvian State and society and the solutions in the international context.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics; kredītu restrukturizācija; Biznesa ideju komercializācija; digitālā transformācija; Ilgtspējīgas attīstība; iedzīvotāju līdzdalība; Sabiedrības novecošanās; sociālā aizsardzība